PENGEMBANGAN MODUL IPA TERPADU MATERI GERAK MELALUI PENDEKATAN KETERAMPILAN PROSES SAINS PADA PESERTA DIDIK KELAS VIII SMP HIKMAH YAPIS JAYAPURA - RISAHONDUA, ITA (Jurnal Ilmu Pendidikan Indonesia, 2018)
Research and Development on Learning using IPA module based on science process skill approach aimed at: (1) knowing how to develop learning module of science. (2) to know the feasibility of developing the learning module of science. (3) to know the advantages and disadvantages of IPA learning module. (4) to know the improvement of learning result by using learning module of IPA. The location of this research was conducted in class VIII SMP Hikmah Yapis Jayapura with 30 students. The results of the validity of module validator obtained by 91.42% with very decent category, the validation of teachers obtained 76.25% with good category, and the results of large-scale module test of 84.17% with very good category. To know the increase of result from science process skill done directly with result of average percentage equal to 80,44% with good category. the result of the average n-gain analysis of class VIII learning result is 0.40 of medium concept concept category, the final analysis result can be concluded that the use of class VIII motion module gives positive impact for the students in learning, so that the science process skill is effectively used in the learning. Keywords: IPA Module, Through Science Process Skills.